2009
DOI: 10.1016/j.jcmg.2008.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Serial Contrast-Enhanced Cardiac Magnetic Resonance Imaging Demonstrates Regression of Hyperenhancement Within the Coronary Artery Wall in Patients After Acute Myocardial Infarction

Abstract: Serial CE-CMR identified changes in spatial extent and intensity of coronary contrast enhancement in patients after AMI. This technique may be useful for the characterization of transient coronary tissue signal changes, which may represent edema or inflammation during the post-infarction phase. In addition, CE-CMR may offer the potential for visualization of inflammatory activity in atherosclerosis associated with acute coronary syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 33 publications
5
82
1
Order By: Relevance
“…The findings of this study regarding strong enhancement of intracranial plaques within 4 weeks of ischemic stroke are similar to the findings for extracranial plaques and may therefore suggest that intracranial enhancement is a marker of inflammation. Inflammation and, therefore, plaque enhancement are expected to decrease in the chronic phase for extracranial vessels, 3,12 and this was also seen in this study.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The findings of this study regarding strong enhancement of intracranial plaques within 4 weeks of ischemic stroke are similar to the findings for extracranial plaques and may therefore suggest that intracranial enhancement is a marker of inflammation. Inflammation and, therefore, plaque enhancement are expected to decrease in the chronic phase for extracranial vessels, 3,12 and this was also seen in this study.…”
Section: Discussionsupporting
confidence: 75%
“…2 In addition to serum markers, the use of noninvasive imaging modalities including CT, MR imaging, and nuclear medicine for the characterization of plaque inflammation has been gaining interest over the past several years. 3,[10][11][12][13][14][15][16][17] Investigations with FDG-PET imaging have shown that it may be used as a surrogate marker for inflammation of plaques, as patients with the highest levels of FDG uptake had the greatest concentrations of inflammatory biomarkers. 10,11 MR imaging characterization of extracranial atherosclerotic plaque has been well studied and well established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A contrast-enhanced approach can also be used for plaque characterization with CMR. Studies using clinically approved extracellular contrast agents showed that uptake in the coronary artery wall is non-specific and could be associated with both atherosclerotic plaque composition and inflammation in patients with stable CAD or acute coronary syndrome [80,81]. Enhancement with newly developed albumin binding and iron oxide-based contrast agents is associated with increased endothelial permeability and thus can be used for coronary wall imaging [82][83][84][85].…”
Section: Coronary Artery Wall Imagingmentioning
confidence: 99%
“…In clinical application, native MRI can differentiate among the morphological components of atherosclerotic plaques in the carotids, the aorta as well as coronary arteries [7 -9]. Additional information regarding plaque composition can be obtained by administering clinically-approved non-specific contrast agents [10]. Specific molecular probes that selectively highlight certain molecules or cells allow the visualization and characterization of pathological processes on the molecular level, thus enhancing the detection of early stages of disease, and improving treatment planning and therapy monitoring.…”
Section: Key Pointsmentioning
confidence: 99%